Digital Expressions: Exploring Cultural Emoticons and Changing Digital Speech Patterns (European Journal of Formal Sciences and Engineering, 2021)
With the development of technology and computing applications, communication among people become easy. Nowadays different platforms are accessible for expressing news, knowledge, and multiple emotions such as happiness, sadness, disappointment, thoughts, opinions. In the current digital world, emoticons play a vital role in computer-based communication. This study examined the usage of emoticons and the slight shift of words to emoticons in computer-mediated communication. The research also investigates how people understand the emoticon, and used them for clearing their meanings. The study investigates participants' views and interpretations of emoticons by utilising a mixed-methods technique that combines surveys and qualitative analysis of communication data. It investigates emoticons' cultural relevance and communication potency while taking into account variables like age, gender, and social environment that affect emoticon usage. The main focus of the study is to identify the demand for emoticons from a cultural perspective. The study is a good contribution from the cultural perspective, as it would help to identify the demand for cultural icons in Pakistan. It helps to understand the language change i.e., replacement of letters to emoticons. The findings have consequences for people, academics, and practitioners, highlighting how crucial it is to take cultural considerations into account when creating communication platforms and comprehending how visual symbols affect message perception. In addition to this study, the frequency usage of emoticons is also investigated.
Keywords: Emoticons, emojis, computer-mediated communication, cultural demand, language change, visual symbols.